A Handbook to Twentieth-Century Musical Sketches - Hall, Patricia; Sallis, Friedemann (New York Cambridge University Press, 2011)
The scholarly study of autograph sources has exploded over the past quarter century especially in the field of twentieth-century music. Yet, few if any courses or seminars broach the subject of sketch studies and the skills required to examine the manuscripts. This book surveys the knowledge necessary to work efficiently in archives and libraries with the skills and techniques specifically related to sketch studies: transcription, reconstructing sketchbooks, deciphering handwriting, and dating documents.
Keywords: 20th Century (1901-2000); Music history